Becoming conversant with the emerging church: understanding a movement and its implications - Carson, D. A. (Zondervan, 2005)
"An exploration and evaluation of the emergent church and how it relates to more traditional forms of worship and theology"--Provided by publisher. - The emerging church profile -- Emergent strengths in reading the times -- Emergent analysis of contemporary culture -- Personal reflections on postmodernism -- Contribution and challenges -- Emergent critique of postmodernism -- Emergent weakness illustrated in two significant books -- Some biblical passages providing perspective for the emerging church -- A biblical meditation on truth and experience.